Evaluation of the labeling of lactose-free dairy products - Eduarda Rodrigues Monteiro; Aline Tiecher (Revista do Instituto de Latícinios Cândido Tostes, 2023)
To meet the needs of individuals with diseases or conditions that require lactose restriction, foods free and low in this carbohydrate are regulated by RDC n.° 135, of February 8th, 2017. Therefore, the objective of this study was to analyze the information contained in the labels of lactose-free dairy products against the main food laws. Labels of different lactose-free dairy products were analyzed, such as UHT milk, milk cream, condensed milk, yogurt, dairy drink, mozzarella cheese, Minas Frescal cheese, cream cheese, milk fudge, and ricotta, totaling 37 products, commercialized in the cities of Itaqui, RS and Francisco Beltrão, PR, from September 2020 to September 2021. Among the irregularities, the lack of homemade measures was verified in 92% of the labels. In 8% of the labels there was no expression “Diabetic: contains (specify the mono- and or disaccharide)” and the guidance “Consumption preferably under the guidance of a nutritionist or doctor”. Only one of the labels (R2) analyzed did not present nutritional information per 100 g or mL. Nonconformity was found regarding labeling on the presence of gluten and mandatory labeling of the main foods that cause food allergies. In addition, all labels had the declaration “lactose free”, “zero lactose”, “0% lactose”, “lactose free” or “lactose-free”, close to the sales denomination of the food. It is concluded that only one product (R3) followed the legislation, emphasizing the importance of the adequacy of the labels by the manufacturers, to guarantee to the consumers clear, correct, and standardized information in accordance with the current legislation.